The integrative relationship between work–family conflict and turnover intention: a meta-analysis - Li, Guanghua; Zhou, Yuhan; Zhang, Xinyue; Martek, Igor (Frontiers in Public Health, 2025)
The impact of work–family conflict on employee turnover intention has become a significant topic in organizational behavior research. However, existing findings show significant discrepancies, lacking systematic quantitative integration. The purpose of this study is to explore the relationships between work–family conflict, work-to-family conflict, family-to-work conflict, and employee turnover intention. It considers the moderating effects of national culture, occupation type, age, gender, and measurement tools. Methodology utilizes meta-analysis of large sample data, based on 122 empirical studies. It is found that: (1) There is a significant positive correlation between overall work–family conflict and turnover intention (r = 0.446), with both work-to-family conflict (r = 0.318) and family-to-work conflict (r = 0.261); (2) National culture (individualism/collectivism), occupation type, and measurement tool differences significantly moderate these three relationships; (3) Age only moderates the relationship between family-to-work conflict and turnover intention, while gender moderation effects are not supported. These findings enrich the knowledge system of turnover intention research and provide practical guidance on the implementation of effective measures to reduce turnover.